Link-disjoint routing algorithm under multiple additive QoS constraints - XIONG Ke1; QIU Zheng-ding1; ZHANG Yu1; ZHANG Hong-ke3 (Tongxin xuebao)
The problem of finding link-disjoint paths under multiple additive QoS constraints was studied.Since the existing algorithms depended on network’s structure and could not guarantee to find feasible solutions for arbitrary net-works,a novel algorithm called multiple constrained link-disjoint path routing algorithm（MCLPRA） was proposed.MCLPRA was based on SAMCRA and didn’t rely on the network’s structure.By introducing the parameter to control its search depth,dividing the solution space into different classes and performing searching according to the classes respectively,MCLPRA was able to obtain the feasible solutions for arbitrary networks.Theoretic analysis shows that MCLPRA can get the feasible and optimal solutions when traditional schemes can not.Comprehensive simulations also show that MCLPRA has better performances than existing algorithms in terms of higher average successful rate of getting feasible solutions with shorter average total length of the obtained path pair.